The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/03009734.2016.1144663
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances among Swedish soldiers after military service abroad

Abstract: AimsSince 1956, more than 100,000 Swedish soldiers have served abroad on various international missions. The aim of this paper was to determine whether there was a connection between military service abroad and sleep disorders among Swedish soldiers.MethodsThe prevalence of sleep disturbances among 1,080 veterans from Kosovo and Afghanistan was compared with almost 27,000 Swedes from a general population sample, using propensity score matching and logistic regression. The sleep disturbances studied were habitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The military part of the questionnaire contained several questions about the participants’ assignments abroad, such as the number of missions abroad, the country of the assignment, whether the participant was deployed in a staff position or served more of the time in the field and whether the participant spent a considerable time in vehicles. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…The military part of the questionnaire contained several questions about the participants’ assignments abroad, such as the number of missions abroad, the country of the assignment, whether the participant was deployed in a staff position or served more of the time in the field and whether the participant spent a considerable time in vehicles. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…SDB patients were diagnosed using the Berlin Questionnaire (BQ) in two studies [34,43], the 9 th and 10 th edition of ICD in three studies PLOS ONE [44][45][46], the 2 nd or 3 rd edition of ICSD in two studies [47,48], the Apnea Hypopnea Index (AHI) in four studies [47][48][49][50], previously documented information in two studies [51,52], self-reported SDB in one study [53], and no diagnose tool in one study [54]. As for the definition of insomnia, two studies used the 9 th and 10 th edition of ICD [44,55], three used the 2 nd and 3 rd edition of ICSD [47,48,56], seven used the ISI [48,[57][58][59][60][61][62], one used the Brief Insomnia Questionnaire (BIQ) [63], four used a self-edited questionnaire [63][64][65][66], two used selfreported data [53,67], and one used documented information [52]. The total sample consisted of 21,923,699 in the military population and 28,223 in the general population.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Whether these physiological cardiac adaptations to repetitive vigorous training on future cardiovascular disease and mortality are beneficial or hazardous to armed forces remain unknown. In addition, several unhealthy behaviors and environments such as cigarette smoking, alcohol intake, stress, insomnia, and depressive mood are prevalent among arm forces, which may affect the physical performance by reducing cardiopulmonary function and increase the risk of hospitalization for acute illness [9,10] . However there were few studies using large military cohorts, particularly of Asian young adults, with detailed data of demographics, laboratory exams, and cardiopulmonary function evaluations at baseline, to follow up the incidence of cardiovascular disease and other severe illness events.…”
Section: Introductionmentioning
confidence: 99%